Final answer:
To expand the logarithm log₂(2x⁶/y), we use the properties of logarithms for products and quotients. Using these rules, the expression is simplified to 1 + 6 · log₂(x) - log₂(y).
Step-by-step explanation:
To fully expand the logarithm log2(2x6/y), we use the properties of logarithms. Specifically, we apply two key rules:
- The logarithm of a product: logb(xy) = logb(x) + logb(y).
- The logarithm of a quotient: logb(x/y) = logb(x) - logb(y).
Applying these rules, we get:
log2(2x6/y) = log2(2) + log2(x6) - log2(y)
Then we apply the rule of logarithms for an exponent, which states logb(xn) = n · logb(x), giving us:
log2(2x6/y) = log2(2) + 6 · log2(x) - log2(y)
Since log2(2) is simply 1 because 2 is the base of the logarithm, the fully expanded form is:
log2(2x6/y) = 1 + 6 · log2(x) - log2(y)